1991
DOI: 10.1007/bf00202460
|View full text |Cite
|
Sign up to set email alerts
|

Expansion ratio effects on the separated shear layer and reattachment downstream of a backward-facing step

Abstract: Experiments were carried out to study the behavior of the incompressible turbulent separated shear layer and subsequent reattachment, downstream of a backward-facing step in a channel. The main objective of the study was to determine the effect of the expansion ratio on the development of the mean velocity and turbulence intensity in the shear layer and on the evolution of wall static pressure downstream of the step. The step height-to-upstream channel height ratio was varied between 0.5 and 2.13 while all inl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
11
0
2

Year Published

1993
1993
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(16 citation statements)
references
References 21 publications
3
11
0
2
Order By: Relevance
“…These results indicated that there was a non-uniform shear layer thickness near the side walls and that the spanwise uniformity of the mean flow was limited to approximately a 50% depth of the channel. This observation was also found in Ötügen [46]. Indeed, Fig.…”
Section: Backward-facing Step Flowsupporting
confidence: 72%
See 3 more Smart Citations
“…These results indicated that there was a non-uniform shear layer thickness near the side walls and that the spanwise uniformity of the mean flow was limited to approximately a 50% depth of the channel. This observation was also found in Ötügen [46]. Indeed, Fig.…”
Section: Backward-facing Step Flowsupporting
confidence: 72%
“…In our experiments, the turbulence intensity of the incoming wall jet reaches approximately 24% of the reference velocity U m . This level was higher than that of the duct flow in the studies of Stevenson et al [58], Vogel and Eaton [61] and Ötügen [46] and strongly enhances the crossstream diffusion momentum [28]. Finally, it is necessary to note that the turbulent wall jet over a backward-facing step in this study is characterized by three length-scales, i.e., the vertical height y m of the inner region, the jet half width Y 1=2 for the wall jet flow, and the step height h for the backward-facing step flow.…”
Section: Backward-facing Step Flowmentioning
confidence: 76%
See 2 more Smart Citations
“…The backward facing step (BFS) has been thoroughly investigated using both numerical simulation and experimental methods. [8,[10][11][12] Comprehensive reviews of previous research on BFS and other separated flows have also been undertaken in the past, [4,13] and a more recent study by Nadge and Govardhan [14] provided a vivid summary of past research activities. Detailed investigations of forward facing step (FFS), on the other hand, are less numerous.…”
Section: Introductionmentioning
confidence: 96%